الخوف والرجاء في القرآن الكريم "سورة الزمر أنموذجا" – دراسة موضوعية - أحمودة, وداد (University of Eloued جامعة الوادي, 2017)
يتطرق هذا البحث إلى دراسة موضوع بعنوان: "الخوف والرجاء في القرآن الكريم ــــــ سورة الزمر أنموذجا"وهذه الدراسة تحاول الكشف عن مدى احتواء سياقات سورة الزمر على جانبي الخوف والرجاء فيها. وقد اشتملت الدراسة على مقدمة ومبحث تمهيدي, وثلاثة مباحث, عني المبحث التمهيدي في تعريف الخوف والرجاء وبيان معاني الألفاظ المرادفة لهما وأثرها في القرآن الكريم, ثم المبحث الأول وعني بالتعريف العام لسورة الزمر ثم المبحث الثاني وعني بتجليات صفة الخوف في سورة الزمر, وكذا المبحث الثالث والذي عني بتجليات صفة الرجاء في سورة الزمر، وطريقة تحقيق الخوف والرجاء في النفوس. وفي الأخير ختمت البحث بخاتمة تضمنت النتائج المتوصل إليها, أذكر من أبرزها: - أن الخوف والرجاء بينهما تلازم عظيم ولا ينفك أحدهما عن الآخر . -أن تدبر في آيات الله القرآنية والكونية, يعد أكبر عون على تحقيق الخوف والرجاء في النفوس This Project deals to the study of the subject entitled “the fear and the please in the Quoran” surat Elzomar as a sample. This study tues to dixover in which extiut does it included in the aspects of the fear and the please inside it. Also, this study includes an introduction, introducing search, three searches. The introducing research deals with the definition of the fear, the pleas and their meaning the speech of the Quoran moreover the relation between them, showing the meaning of the words which are equivalent to them and their effects in the Quoran. Then, the first research which deals with the definition as a completion to surat Elzomar. After that, the second research that deals with the analysis of the dexriptive word fear in surat Elzomar. Next, the third research that deals with the analysis of the dexriptive word please and the way to realize the fear and the in the souls. Finally, we and this research with a conclusion that shows the (reached) obtained results: - Fear from Allah is as an aid for the believer to educate himself obedience's and subsiding from offends and sins. - Hope inculcates in the believer's heart hope and good intention of Allah, and it leads him to arriving and asking for Allah the Exalted, the majestic
مذكرة ماستر تخصص تفسير علوم القرآن
Keywords: الخوف ـــ الرجاء ــ سورة الزمر ـــ القرآن; problems- Islamic - Muhammad FethullahGülen - .Malik bin Nabi